Many Faces of Bronchiolitis and Organizing Pneumonia - Cordier, Jean-François; Cottin, Vincent; Lazor, Romain; Thivolet-Béjui, Françoise (Seminars in Respiratory and Critical Care Medicine, 2016)
As the bronchioles have a strategic position between the airways and the alveolar structures, they are at a site where disorders of many origins may develop, including infections, inflammatory and/or fibrosing processes of immune, occupational, environmental, tumoral, and iatrogenic origin, which may result in predominant bronchiolitis and/or organizing pneumonia. This etiologic variety results in many distinct entities and syndromes, common or rare, with new or renewed faces such as bronchiolocentric interstitial pneumonia or organizing pneumonia primed by radiation to the breast.
Keywords: bronchiolitis; postinfectious bronchiolitis; bronchiolitis obliterans syndrome after transplantation; organizing pneumonia; bronchiolocentric interstitial pneumonia